Strategi Pemasaran Untuk Meningkatkan Penjualan Kopi Nako Kebon Jati Bogor - Erwin Permana; Muhamad Athalah Ramadhan; Ifnu Saputra; Syamsurizal, Syamsurizal (Pusat Riset dan Inovasi Nasional, 2024)
Businesses that combine environmental and product aspects are currently growing quite rapidly. Consumers are not only served products according to their taste but can also enjoy natural views with fresh air. One business that utilizes natural aspects as a marketing strategy is Kopi Nako Kebon Jati. This research aims to analyze marketing strategies to increase sales of Kopi Nako Kebon Jati Bogor. The research was conducted using a qualitative descriptive approach. Data comes from analysis of the results of literature reviews and related official publications. The results of this research show that the marketing used by Kopi Nako Kebon Jati Bogor is the Marketing Mix which consists of 4Ps, namely product, price, place and promotion. Of these four things, efforts are made to maximize product marketing strategies. After that, it is supported by a social media platform via the Kopi Nako Kebon Jati Instagram account. This Instagram aims to provide useful information for consumers and reach a very wide market, so that it can increase sales of Kopi Nako Kebon Jati Bogor. The unique strategy that differentiates Kopi Nako Kebon Jati from the others is Hidden Gem, namely that they take a place quite far from the city center and make it a special attraction for Kopi Nako Kebon Jati which sells views of Mount Salak which are not available in coffee shops in general.